The mechanism of hypolimnion warming induced by internal waves. (26th May 2015) - Nishri, Aminadav; Rimmer, Alon; Lechinsky, Yury
Abstract The measured temperature of the hypolimnion of Lake Kinneret, Israel, reveals an average rise of ∼0.6 ± 0.3°C between April and December. Three mechanisms are suggested as the cause of this rise: (i) direct radiation; (ii) an entire‐lake vertical diffused heat transfer; and (iii) a mechanism of "indirect warming, " which is investigated here for the first time. The indirect warming mechanism prevails in the sublittoral zones, which are affected by internal seiche activity, including Poincare and Kelvin waves with cycle periods of ∼12 h and ∼24 h, respectively. During part of the seiche's time span, the warm epilimnetic water comes into contact with the underlying bottom sediments and heats them. During the rest of the seich's cycle, part of the sublittoral bed sediments become overlain by cold hypolimnetic water and cause the previously heated sediments to emit most of their heat, slightly warming the hypolimnion. The daily cycle of this indirect warming mechanism is superimposed on the seasonal cycle of the sublittoral bed sediments, which are cold in the winter and warm in the summer, in accordance with the seasonal pattern of the epilimnion's temperature. Empirical evidence that suggests that indirect warming actually takes place in response to well‐documented seiche water motions is presented in this article. For example, according to the proposed analysis of sediment temperature changes, in the month of June a daily heat flux of 7.88 W m−2 (0.68 MJ m−2 d−1) was estimated. It was found that during the first 5 months of stratification this mechanism contributes ∼41% of the thermal energy needed for the 0.6°C temperature increase. This mechanism is expected to occur at any thermally stratified lake that is significantly affected by internal seiche activity.